The Effect of Tax Awareness Level and Tax Service Effectiveness on Taxpayer Compliance in Sukabumi Regency - Tiara Nurul Hikmah; Vita Citra Mulyandini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the effect of Taxpayer Awareness and the Effectiveness of Tax Services on Taxpayer Compliance in Sukabumi Regency. This research employs a quantitative approach using primary data collected through structured questionnaires distributed to taxpayers. The population of this study consists of PBB-P2 taxpayers who visited the Regional Revenue Agency (BAPENDA) of Sukabumi Regency, with a total sample of 100 respondents selected using accidental sampling. Data were analyzed using multiple linear regression with the assistance of SPSS software. Prior to hypothesis testing, classical assumption tests, including normality, multicollinearity, and heteroskedasticity tests, were conducted to ensure the suitability of the regression model. The results of the study indicate that Taxpayer Awareness has a negative and insignificant effect on Taxpayer Compliance. In contrast, the Effectiveness of Tax Services has a positive and significant effect on Taxpayer Compliance. Furthermore, Taxpayer Awareness and the Effectiveness of Tax Services simultaneously have a positive and significant effect on Taxpayer Compliance. These findings suggest that improving the quality and effectiveness of tax services plays a more critical role in enhancing taxpayer compliance than awareness alone. The results of this study provide empirical evidence for tax authorities to prioritize service quality improvements as a strategic approach to increasing taxpayer compliance. This study also contributes to the literature by highlighting the relative importance of institutional service factors compared to individual awareness in shaping compliant taxpayer behavior.